Sensorineural Hearing Loss Due to Exposure of Noisy Trains on Populations Around Turirejo Train Railroad Cross - Diana Kusuma Wardhani; Jojok Mukono Mukono (Universitas Airlangga, 2020)
Introduction: As one of the preferred modes of land transportation, the frequency of train services was very high. One of the negative impacts arising from train activity was noise. The high noise intensity of the train causes hearing loss. Method: This study aims to analyze the differences in the incidence of hearing loss in 2 groups of residents in Turirejo Lawang Malang. This research used the observational method and the data were analyzed descriptive qualitative. A total of 20 people were selected as respondents by purposive sampling. Noise intensity was measured by Sound Level Meter and audiometric measurements were examined at SIMA Malang Laboratory. Result and Discussion: The prevalence of sensorineural hearing loss was more common in residents whose homes at 3-7 m away from the railroad tracks. In addition, residents who lived at least 15 years at a distance of 3-7 m also experienced more hearing loss. One cause of hearing loss is due to exposure to high noise and for a long time and will damage the hair cells in the cochlea, causing hearing loss. If noise exposure continues and for a long period of time damage to hair cells will be permanent and cannot return to normal. Conclusion: There needs to be a policy from the government in determining the minimum limit of the distance of the house to the railroad tracks. In addition, it is necessary to install a barrier near people's homes to reduce noise.